2023
DOI: 10.1002/adma.202211871
|View full text |Cite
|
Sign up to set email alerts
|

BN‐Bond‐Embedded Triplet Terpolymers with Small Singlet–Triplet Energy Gaps for Suppressing Non‐Radiative Recombination and Improving Blend Morphology in Organic Solar Cells

Abstract: Suppressing the photon energy loss (Eloss), especially the non‐radiative loss, is of importance to further improve the device performance of organic solar cells (OSCs). However, typical π‐conjugated semiconductors possess a large singlet–triplet energy gap (ΔEST), leading to a lower triplet state than charge transfer state and contributing to a non‐radiative loss channel of the photocurrent by the triplet state. Herein, a series of triplet polymer donors are developed by introducing a BNIDT block into the PM6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Moreover, fine tailoring of the molecular structure will effectively modulate the radical characters of donors/acceptors, which can be demonstrated by the obvious changes in chemical/physical properties in OSCs. It will be of great importance to achieve high-performance near-infrared emitters with excellent photovoltaic device performance and stability. Our studies provided a novel and important guideline for the design of donors and acceptors in OSCs.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, fine tailoring of the molecular structure will effectively modulate the radical characters of donors/acceptors, which can be demonstrated by the obvious changes in chemical/physical properties in OSCs. It will be of great importance to achieve high-performance near-infrared emitters with excellent photovoltaic device performance and stability. Our studies provided a novel and important guideline for the design of donors and acceptors in OSCs.…”
Section: Discussionmentioning
confidence: 94%
“…[ 1–3 ] Thanking for the success of the A–D–A and A–DA′D–A type nonfullerene acceptors (NFAs) possessing strong near infrared (NIR) absorptions and fibril‐like molecular packings, [ 3–7 ] OSCs have witnessed rapid progress in the last few years with meteoric rise of power conversion efficiencies (PCEs) exceeding 19%. [ 8–22 ] In addition to NFAs, the development of new donors is equally important for achieving highly efficient OSCs. However, in contrast to the booming growth of NFAs, the development of matched and excellent wide bandgap (WBG) polymer donors lags relatively behind.…”
Section: Introductionmentioning
confidence: 99%
“…DOI: 10.1002/adma.202300631 molecular packings, [3][4][5][6][7] OSCs have witnessed rapid progress in the last few years with meteoric rise of power conversion efficiencies (PCEs) exceeding 19%. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In addition to NFAs, the development of new donors is equally important for achieving highly efficient OSCs. However, in contrast to the booming growth of NFAs, the development of matched and excellent wide bandgap (WBG) polymer donors lags relatively behind.…”
mentioning
confidence: 99%
“…Different from the red‐shifted shoulder peaks that are generally considered as a result of molecular aggregation, [21–23] there is no consensus about the origin of SWR shoulder peaks. Some studies revealed that the existence of multiple donor–acceptor (D–A) intramolecular charge transfer (ICT) processes in the backbone of conjugated molecules can separate the spatial distribution of the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) to respectively localize on different molecular moieties [24] . The decreased overlap between HOMO and LUMO partially forbids the HOMO→LUMO transition and allows more higher‐energy transitions, therefore increasing the oscillator strength of SWR absorption band [25] .…”
Section: Introductionmentioning
confidence: 99%